News consumption and political party preferences in Poland - Wenzel, Michał (Political Preferences, 2018)
The objective of this paper is to determine the scale of influence of the media (both traditional and social) on party preferences. The complicated contemporary media ecosystem, in which the boundaries between traditional and internet media are blurred (internet versions of newspapers), news coverage is increasingly de-professionalized (emergence of civic journalism), verification of information becomes increasingly problematic (fake news) leads to a number of theoretical and methodological challenges. Theoretically, the paper uses the model in which mass media act as a factor triggering the emergence of latent views. Empirically, the effort is undertaken to cover the whole universe of information sources, including both print and electronic media, both traditional and internet sources. The analysis determines citizens’ sources of information, tracks consistencies in selecting particular categories of sources (thus outlining ‘information bubbles’), correlates sources with party preferences and measures generalized attitudes to media categories. The study is undertaken on a sample representative for adult Polish population, fielded with CAWI methodology. Key words: mass media, political attitudes, news, public opinion